Giant appendiceal mucinous cystadenoma treated by laparoscopy: a case report and review of the literature - Nogueira,Felipe Ramos (2017)
ABSTRACT Appendiceal mucinous cystadenoma is a rare entity, which causes appendicular mucocele. It is more frequent in women over 50 years old. In half of the cases it is asymptomatic. Tomography of the abdomen is the gold standard in its preoperative diagnosis. The treatment is surgical, with good prognosis, the complete resection evolves without appendicular rupture and extravasation. We report a case of a 64-year-old man with appendiceal mucinous cystadenoma. A laparoscopic right hemicolectomy was performed. This therapy that can be safely used to treat appendiceal mucocele, as long as it is cautious.